Comparative genomic profiling of transport inhibitor Response1/Auxin signaling F-box (TIR1/AFB) genes in eight Pyrus genomes revealed the intraspecies diversity and stress responsiveness patterns - Yang, Sheng; Yu, Xiaomei; Gao, Xinke; Fatima, Kinza; Tahir Ul Qamar, Muhammad (Frontiers in Genetics, 2024)
In the genomics of plants and the phytoecosystem, Pyrus (pear) is among the most nutritious fruits and contains fiber that has great health benefits to humans. It is mostly cultivated in temperate regions and is one of the most cultivated pome fruits globally. Pears are highly subjected to biotic and abiotic stresses that affect their yield. TIR1/AFB proteins act as auxin co-receptors during the signaling of nuclear auxins and play a primary role in development-related regulatory processes and responses to biotic and abiotic stresses. However, this gene family and its members have not been explored in Pyrus genomes, and understanding these genes will help obtain useful insights into stress tolerance and ultimately help maintain a high yield of pears. This study reports a pangenome-wide investigation of TIR1/AFB genes from eight Pyrus genomes: Cuiguan (Pyrus pyrifolia), Shanxi Duli (P. betulifolia), Zhongai 1 [(P. ussuriensis × communis) × spp.], Nijisseiki (P. pyrifolia), Yunhong No.1 (P. pyrifolia), d’Anjou (P. communis), Bartlett v2.0 (P. communis), and Dangshansuli v.1.1 (P. bretschneideri). These genes were randomly distributed on 17 chromosomes in each genome. Based on phylogenetics, the identified TIR1/AFB genes were divided into six groups. Their gene structure and motif pattern showed the intraspecific structural conservation as well as evolutionary patterns of Pyrus TIR1/AFBs. The expansion of this gene family in Pyrus is mainly caused by segmental duplication; however, a few genes showed tandem duplication. Moreover, positive and negative selection pressure equally directed the gene’s duplication process. The GO and PPI analysis showed that Pyrus TIR1/AFB genes are associated with abiotic stress- and development-related signaling pathways. The promoter regions of Pyrus TIR1/AFB genes were enriched in hormone-, light-, development-, and stress-related cis elements. Furthermore, publicly available RNA-seq data analysis showed that DaTIR1/AFBs have varied levels of expression in various tissues and developmental stages, fruit hardening disease conditions, and drought stress conditions. This indicated that DaTIR1/AFB genes might play critical roles in response to biotic and abiotic stresses. The DaTIR1/AFBs have similar protein structures, which show that they are involved in the same function. Hence, this study will broaden our knowledge of the TIR1/AFB gene family in Pyrus, elucidating their contribution to conferring resistance against various environmental stresses, and will also provide valuable insights for future researchers.